1989
DOI: 10.2307/1387248
|View full text |Cite
|
Sign up to set email alerts
|

Evangelical Politics and Status Issues

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
25
0

Year Published

1989
1989
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 22 publications
0
25
0
Order By: Relevance
“…Most often, these studies seek to either explore or control for the seemingly unique role of the South in American politics. There is evidence that region matters: Being from the South is correlated with support for the Christian right (Wald et al 1989) and with conservative theological views (Davis & Robinson 1996a). In an article on conservative Protestantism, Woodberry & Smith (1998) found that (we assume white, although race is not specified) evangelical and fundamentalist Christians living in the South held more socially conservative views than their counterparts in the North.…”
Section: The Complexity Of Religion and Placementioning
confidence: 99%
“…Most often, these studies seek to either explore or control for the seemingly unique role of the South in American politics. There is evidence that region matters: Being from the South is correlated with support for the Christian right (Wald et al 1989) and with conservative theological views (Davis & Robinson 1996a). In an article on conservative Protestantism, Woodberry & Smith (1998) found that (we assume white, although race is not specified) evangelical and fundamentalist Christians living in the South held more socially conservative views than their counterparts in the North.…”
Section: The Complexity Of Religion and Placementioning
confidence: 99%
“…Antiracist educators are attempting to create a more just world through appropriate standards of behavior and a commitment to activism. They have a more or less coherent program for social change, involving the transformation of how the public understands race relations (Applebaum 1997;Bonnett 1996;Eichstedt 2001;McMahon 2003;Scott 2000;Srivastava 2005;Srivastava and Francis 2006;Wald et al 1989;Warren and Hytten 2004;Zajicek 2002). In order to do so, antiracist educators have 1) constructed an ontological foundation on which the problem racism is grounded, aided by an epistemic culture that is expressed as an estrangement from dominant values; 2) spread a moral panic in which the threat posed by whites to minorities has been amplified; 3) offered a diagnosis of the problem and its causes; and 4) advocated for particular actions that they assert would alleviate the problem.…”
Section: A Broader Viewmentioning
confidence: 99%
“…Antiracist education's rapid growth may be attributed, at least in part, to the fact that its proponents are located within settings that have so-called "mobilizing structures," including academic departments, schools, professional societies, and peer networks that develop common understandings, create a collectivist orientation, coordinate activities, and lend urgency to the matter (Frickel and Gross 2005;Snyder 2004;cf. Clarke 1987;Wald et al 1989).…”
Section: A Broader Viewmentioning
confidence: 99%
“…First, the social status of doctrinally conservative religious groups is both ambiguous and controversial (see especially Wald et al 1989). As such, fundamentalist identification provides an interesting intermediate case between the &dquo;subordinate&dquo; and &dquo;dominant&dquo; groups examined by Miller et al Second, attempts to make a fundamentalist group identification the basis of political mobilization have included descriptions of disliked out-groups.…”
mentioning
confidence: 99%